HUMAN RIGHTS RELATED TO THE RIGHT TO RELIGION AND ECONOMY IN THE CONFLUENCE OF CULTURES - MAGIRU, Anca; CIOBANICA, Mihaela Lavinia; DANECI-PATRAU, Daniel; NEGURITA, Octav (Annals of Spiru Haret University. Economic Series, 2018)
The paper is focused on the authors’ opinion, based on deep research, that religion and education go side by side and could help a lot and should be the basic law for the development, rural or urban, against the background of the nowadays European challenges. Europe confronts today with oncoming waves of immigrants from all over the world who have been invading it for several years, bringing with them cultures, customs, observances, different in many ways from ours. Under these circumstances, the authors would like to highlight their point of view, mainly the idea that the words of Martin Luther King Jr.: “Hate paralyzes life; love releases it. Hate confuses life; love harmonizes it”, are much more true than ever. To keep an open mind on religious education, to be flexible, loving and understanding should be of vital importance in developing rural communities against the background of the European competitiveness.